2003
DOI: 10.1023/a:1022019813078
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: To modify the surface of poly(L-lactide) (PLA) supports, we have investigated the feasibility to deposit on the PLA surface Langmuir-Blodgett films of amphiphilic block copolymers based on poly(L-lactide). AB and ABA block copolymers were prepared with PLA as the A block and either poly(ethylene oxide), alpha-methoxy-omega-hydroxy poly(ethylene oxide), alpha-carboxy-omega-hydroxy poly(ethylene oxide) or poly(L-aspartic acid) as the B blocks. Films with phase-separated hydrophilic and hydrophobic blocks in a bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…Considering the twisting of polymer backbones, these arms had the similar length to one part of BBCP, either the PS part or the PLA part described previously. It has been reported that both PS and PLA are able to form the spreading phase at the air/water interface. Therefore, to identify which part of BBCP composed the dot-like domain and the other formed the spreading phases adjacent to it, thermal annealing study was performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the twisting of polymer backbones, these arms had the similar length to one part of BBCP, either the PS part or the PLA part described previously. It has been reported that both PS and PLA are able to form the spreading phase at the air/water interface. Therefore, to identify which part of BBCP composed the dot-like domain and the other formed the spreading phases adjacent to it, thermal annealing study was performed.…”
Section: Resultsmentioning
confidence: 99%
“…With the increase in surface pressure (i.e., in the liquid state region ii in Figure a), there was a strong elastic repulsive force between the PLA parts; this is analogous to the behavior of spreading phase in amphiphilic block copolymers. , As a result, a continuous pressure increase was observed in this region. However, due to the intrinsic hydrophobic nature of PLA, it can hardly be expelled into the water subphase to form brush-like morphology as commonly seen in amphiphilic block copolymers. Thus, PLA arms that surrounded the PS domain had to rearrange themselves to release the elastic stress (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…The contact angle of the modified surface varied with the feed composition [163]. Other functional groups such as hydroxyl, carboxyl and amide groups, have also been introduced onto PLLA surfaces, using the photo-induced grafting method, by grafting hydroxyethyl methacrylate, methacrylic acid (MAA) or acrylamide, respectively [164].…”
Section: Photo-induced Grafting Methodsmentioning
confidence: 99%
“…Such modification can be investigated by applying the Langmuir monolayer approach. For example, the surfaces of a spin-casted PLA film, functionalized by LB-layers of amphiphilic AB or ABA block copolymers of PLA as A block and either PEO, a-methoxy-v-hydroxy PEO, a-carboxy-v-hydroxy PEO or poly(Laspartic acid) as B block, improve the protein and cell adhesion [157]. The simulation of the biomolecule impact, such as proteins or enzymes, on a pre-existing synthetic polymer layer is discussed in this section on the microscopic and macroscopic level.…”
Section: Polymer-protein Interactions At the Air-water Interfacementioning
confidence: 99%